Artesunate Ameliorates Experimental Autoimmune Encephalomyelitis by Inhibiting Leukocyte Migration to the Central Nervous System - Thome, Rodolfo; Carvalho, Ana Carolina de; Costa, Thiago Alves da; Watanabe Ishikawa, Larissa Lumi [UNESP]; Campos Fraga-Silva, Thais Fernanda de [UNESP]; Sartori, Alexandrina [UNESP]; Rodrigues de Oliveira, Alexandre Leite; Verinaud, Liana (Wiley-Blackwell, 2016)
Background and Aims: Experimental autoimmune encephalomyelitis (EAE) is T-celldependent disease of the central nervous system (CNS) of mice. This model resembles multiple sclerosis (MS) in many aspects. Therapies that focus in the modulation of the immune response and cellular infiltration in the CNS present best effects in the clinics. Artesunate (Art) is a semi-synthetic sesquiterpene derivative from artemisinin and has been shown to reduce the clinical signs of autoimmune disease models through mechanisms not yet understood. In this study, we aimed to evaluate whether administration of Art would ameliorate EAE. Methods and Results: C57BL6 mice were immunized with MOG(35-55) peptide to induce EAE. At the same time, Art treatment started (3 mg/kg/day via i.p.) for five consecutive days. We found that Art treatment reduced the clinical signs of EAE and that correlated with a reduced infiltration of cells in the CNS. Disease amelioration did not correlate with immunomodulation as recall responses, leukocyte subpopulations, and gene expression analysis were similar among treated and untreated mice. Ultimately, further analysis provided data indicating that a possible mechanism of action for Art is dependent on the cellular migration to the CNS. Conclusions: Artesunate reduces the severity of EAE by inhibiting migration of pathogenic T cells to the CNS.